Colisões Kink-Antikink no modelo 𝜙4 na presença de impureza - SOARES, Maurício Antônio Coutinho (2024)
In this dissertation, we conduct a theoretical analysis of scalar fields in physics. We also study the Bogomol’nyi-Prasad-Sommerfield equation, which is used to obtain the solution to the equation of motion, in addition to the study of topological defects. An analysis of the ϕ4 model was performed based on collisions of the kink-antikink pair, generated various results such as two-bounce windows and bions. At the core of the work, we couple the ϕ4 model with the impurity σj, whose effect can be controlled through it’s amplitude. Such coupling leads to different phenomena, known as spectral walls, which attract the pair, and vacuum walls, which repel the pair, influencing the action of the kink-antikink pair. As a result, new outcomes are observed, such as trapping between the walls. These walls act as a barrier in the pair’s evolution, where the spectral wall arises when the kink’s oscillation mode enters the continuous spectrum, and the vacuum wall arises where the vacuum of the original model is localized.